2022
DOI: 10.55131/jphd/2022/200311
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with infertility among married women in Rajshahi City, Bangladesh

Abstract: Infertility has become a growing problem among reproductive aged women in both developing and developed countries. Recent statistics indicate a significant number of married couples suffering from infertility and visiting infertility centers has increased in Bangladesh. Therefore, this study aims to identify the factors associated with infertility in Bangladeshi women. This is a retrospective study and data were collected from 450 reproductive aged women purposively using a structured questionnaire from an inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…primary or secondary infertility (12). However, another study found a signi cant association between the duration of contraceptive use and infertility, reporting that couples using contraceptive methods for more than two years had an increased risk of infertility (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…primary or secondary infertility (12). However, another study found a signi cant association between the duration of contraceptive use and infertility, reporting that couples using contraceptive methods for more than two years had an increased risk of infertility (11).…”
Section: Discussionmentioning
confidence: 99%
“…The most important reasons for the decline in fertility are the postponement of the rst birth and longer intervals between births (9, 10). One study found that couples who used contraceptive methods for more than two years had an increased risk of infertility (11). On the other hand, some studies have concluded that intentional delay of childbearing is not associated with fertility (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In her study, Nahar (2015) conveyed that in urban Bangladesh, the quality of biomedical treatment is inconsistent, inadequate, and unregulated. The infertility experts of Bangladesh have explained the worth of the treatment considering the high growth of infertility in the country but showed their concern in the quality and quantity of the treatment considering the population size of this developing country (Khatun et al, 2022). However, they pose that both financial and social constraints to biomedical treatment need to be disentangled for a healthier mass, keeping in mind that reproduction is a human right.…”
Section: Theoretical Perspectives and Relevant Literaturementioning
confidence: 99%